2011
DOI: 10.2203/dose-response.11-025.raja
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response of MTLN3 Cells to Serial Dilutions of Arsenic Trioxide and Ionizing Radiation

Abstract: ᮀ MTLn3 cells derived from mouse mammary epithelium are known to be highly malignant and are resistant to both radio-and chemo-therapy. We exposed MTLn3 cells to various doses of inorganic Arsenic trioxide (As 2 O 3 ) in combination with ionizing radiation. Cells were treated with a series of As 2 O 3 concentrations ranging from 20 µM to 1.22 nM for 8 hour, 24 hour and 48 hour periods. Post-treated cell proliferation was quantified by measuring mitochondrial activity and DNA analysis. Cells exposed to radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The hormesis of As 2 O 3 has also been demonstrated by other research groups ( 10 , 25 ). It was reported that a low dose of As 2 O 3 could stimulate osteoblast and MTLn3 cell proliferation ( 10 ). Wang et al ( 27 ) demonstrated that hERG protein expression is associated with tumor-cell proliferation and cancer development.…”
Section: Discussionsupporting
confidence: 69%
“…The hormesis of As 2 O 3 has also been demonstrated by other research groups ( 10 , 25 ). It was reported that a low dose of As 2 O 3 could stimulate osteoblast and MTLn3 cell proliferation ( 10 ). Wang et al ( 27 ) demonstrated that hERG protein expression is associated with tumor-cell proliferation and cancer development.…”
Section: Discussionsupporting
confidence: 69%
“…In that case, looking to a very low dose range might reveal a beneficial hormetic dose range for their adaptation-stimulating effects in most organisms. Thus, it makes sense to look for hormesis at extremely low doses of bulk form arsenic (Raja et al, 2013) and perhaps even lower doses of nano-arsenic trioxide (Ahn et al, 2013). Other nanomaterials such as nano-calcium hydroxyapatite may be largely benign across a wider range of dose levels (Zhou and Lee, 2011) and/or can safely deliver nano-forms of less toxic agents for greater bioavailability and clinical benefit than reliance on more toxic bulk form drugs (Chun et al, 2012;Joshi and Muller, 2009;Koning and Krijger, 2007;Lanao et al, 2007;Moulari et al, 2013;Zhao and Feng, 2010).…”
Section: Nanoparticles and Hormesis In Complex Adaptive Systemsmentioning
confidence: 99%
“…Variability in particle surface properties and materials involved in NP stabilization might contribute to previous findings of variability over time in UV-vis findings on HMs versus controls [85,169,170]. Finally, subsequent research should also evaluate the nanostructure and surface stability characteristics of HMs as correlates of their biological activity [26,27,31,32,132,133,[171][172][173][174] in comparison with succussed and unsuccussed controls [65,78,141,175]. Prior research has demonstrated low-dose hormetic effects triggered in recipient organisms by NPs of various source materials [132][133][134]149,171].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, subsequent research should also evaluate the nanostructure and surface stability characteristics of HMs as correlates of their biological activity [26,27,31,32,132,133,[171][172][173][174] in comparison with succussed and unsuccussed controls [65,78,141,175]. Prior research has demonstrated low-dose hormetic effects triggered in recipient organisms by NPs of various source materials [132][133][134]149,171]. Consequently, examining NPs in various HMs, especially at higher homeopathic potencies such as 30C and 200C (i.e., low conventional doses), for these types of lowdose-dependent, nonlinear dose-response patterns, rather than direct pharmacological ligand-receptor effects, merits further investigation [31,131,142,176].…”
Section: Discussionmentioning
confidence: 99%